Parental Education Matters for Adolescent Health: The Importance of Parental Education in the US - Yu, Jia (Journal of Studies in Social Sciences, 2015)
Parental Education Matters for Adolescent Health: The Importance of Parental Education in the US
Keywords: dept.eco

The Effect of Advertising and In-Store Promotions on the Demand for Chocolate - Patalinghug, Jason (International Journal of Economics and Finance, 2015)
This paper analyzes the effect of TV advertising and in-store displays on the sales of chocolates. I examine which method is more effective in gaining customers and in increasing total sales. Also, I look at the evidence to see whether the lack of advertising by a firm will hurt the industry as a whole. In this paper, I use a nested logit model on scanner data obtained by the Zwick Center for Food and Resource Policy at the University of Connecticut to examine the effect of TV advertising on chocolate sales. The results show that in-store displays and advertising both help increase the demand for chocolate.
Keywords: dept.eco

Does Agglomeration Matter Everywhere?: New Firm Location Decisions in Rural and Urban Markets - Artz, Georgeanne M.; Kim, Younjun; Orazem, Peter F. (Journal of Regional Science, 2016)
We test whether commonly used measures of agglomeration economies encourage new firm entry in both urban and rural markets. Using new firm location decisions in Iowa and North Carolina, we find that measured agglomeration economies increase the probability of new firm entry in both urban and rural areas. Firms are more likely to locate in markets with an existing cluster of firms in the same industry, with greater concentrations of upstream suppliers or downstream customers, and with a larger proportion of college-educated workers in the local labor supply. Firms are less likely to enter markets with no incumbent firms in the sector or where production is concentrated in relatively few sectors. The same factors encourage both stand-alone start-ups and establishments built by multiplant firms. Commuting decisions exhibit the same pattern as new firm entry with workers commuting from low to high agglomeration markets. Because agglomeration economies are important for rural firm entry also, policies encouraging new firm entry should focus on relatively few job centers rather than encouraging new firm entry in every small town.
Keywords: dept.eco

U.S. Macroeconomic News and International Stock Prices: Evidence from Newspaper Coverage - Birz, Gene; Dutta, Sandip (Accounting and Finance Research, 2016)
Existing studies provide mixed evidence that the U.S. macroeconomic news impacts international stock prices. We believe this may be related to the fact that economic surprises may not capture how investors interpret macroeconomic releases in various economic conditions. Consequently, we follow Birz and Lott (2011) and use newspaper coverage of economic releases as a measure of news. We argue that in addition to capturing the surprise component of macroeconomic releases, newspaper coverage provide interpretation of these releases similarly to how investors may interpret them in various economic conditions. Out of 15 examined international stock markets, we find that the U.S. macroeconomic news impacts stock returns of 12 countries.
Keywords: dept.eco

Performance of State-Owned Enterprises: A Comparative Analysis of Ethiopian Airlines and Ghana Airways - Andoh, Samuel K.; Gebremariam, Yilma; Thorson, James; Bodo, Peter (American Journal of Management, 2019)
This paper examines the performance of two state-owned airlines: Ethiopian Airlines and Ghana Airways. While Ethiopian Airlines continues to operate successfully, the other airline has gone out of business. In an industry characterized by heavy competition and a high rate of failure, the success of the state- owned Ethiopian Airlines is intriguing. The evidence shows that Ethiopian Airlines outperforms the industry on some important benchmarks. These findings suggest that being a state enterprise is not necessarily a characteristic that leads to failure. Corporate culture and governance appear to be important factors in the success of Ethiopian Airlines.
Keywords: Airlines; Business And Economics--Management; Business metrics; Economic growth; Economic theory; Emerging markets; Failure; Profits; Public enterprise; Stockholders; Success; dept.eco; peer-reviewed; ⛔ No DOI found

Exchange Rate Management in Advanced Transition Economics - Grubacic, Sanja (2017)
The purpose of my sabbatical leave was to enable me to engage in writing a manuscript on Exchange Rate management in Advanced Transition Economics. This project involved gathering, analyzing, and preparing for publishing the new empirical evidence on behavior of exchange rates in several economies of East and Central Europe. The analysis intended to contribute to a theoretical and empirical literature on the importance of foreign exchange markets and exchange rate management in promoting a country's internal and external balance.
Keywords: dept.eco; faculty_collection; sabbatical_report

Essentials of Money, Banking and Financial Institutions: With Applications to the Developing World - Andoh, Samuel K. (Lexington Books, 2014)
Essentials of Money, Banking and Financial Institutions builds on the essential concepts of money and banking and applies them in the context of developing countries. Frequent comparisons between developed and developing countries are made to enable students to make proper inferences about the efficacy of certain concepts.
Keywords: Developing countries; Developing countries; Banks and banking; Developing countries; Economic development; Finance; Money market; dept.eco; faculty_collection

MADness in the method: On the volatility and irregularity of technology diffusion - Bodo, Peter (Technological Forecasting and Social Change, 2016)
The paper investigates how some drivers of technology diffusion shape the volatility and irregularity of the diffusion process. It presents an agent-based simulation model of technology diffusion that includes variables to control technology generations, social pressures, market size, and network randomness. Several variable combinations are defined, technology diffusions are simulated, and the volatility and irregularity of the process are measured. The paper explores scenarios with unusually high volatility and/or irregularity in more detail. It shows that technology generations mostly affect volatility, social pressures impact irregularity, while network randomness and market size amplify the other two factors' effects. Also, the paper argues that market structure changes generated by the factor combinations in question indirectly affect diffusion volatility and irregularity and these indirect effects may explain very high levels of, and unexpected changes in the volatility and irregularity of the technology diffusion process. (C) 2016 Elsevier Inc All.rights reserved.
Keywords: Agent-based model; Agent-based models; Agent-based simulation models; Autonomous agents; Brand and product category competition; Commerce; Computational methods; Control technologies; Diffusion; Diffusion process; Economic and social effects; Market structures; Network randomness; Product categories; Random processes; Several variables; Technology diffusion; Technology generations; competition (economics); dept.eco; network analysis; numerical model; technology diffusion

Ownership structure, non-interest income and bank risk in ghana - Abugri, Benjamin A; Osah, Theophilus Teye; Andoh, Samuel (Banking and Finance Review, 2016)
This study investigates the relationship between bank ownership structure, non-interest income and risk in an emerging market setting. Our analysis shows that the relationship between product diversification and bank risk is significantly influenced by asset size and ownership structure. In contrast to large banks, small banks are exposed to higher risk when the income share of non-traditional banking activities rise. We also find strong evidence of differences in risk exposure of banks to non-interest income after controlling for ownership structure. Private domestic and private foreign banks experience lower risk with higher non-interest income while the converse is true for public domestic banks. Furthermore, we show that the speed with which risk adjust to non-income activities is faster for domestic private banks than for foreign banks. These results could provide useful information to investors and regulators of banking institutions as they seek to reconcile the important issues of bank ownership structure, income diversification and size on the one hand with the level of risk exposure on the other hand. © 2016, Banking and Finance Review.
Keywords: Bank risk; Ghana; Non-interest income; Ownership structure; dept.eco; dept.fin; ⛔ No DOI found

Sustainable growth with irreversible stock effects of renewable resources - Lopez, Ramon; Yoon, Sang Won (Economics Letters, 2016)
This paper examines sustainability conditions when the stock effects of renewable resources prevail, and characterizes the maximal critical level of initial pollution emissions such that Pigovian tax alone ensures sustainable growth. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Optimal pollution tax; Renewable resources; Stock effects; Sustainable growth; dept.eco

Real exchange rates in advanced transition economies - Grubacic, Sanja; Schuster, Julian (Journal of Eastern European and Central Asian Research (JEECAR), 2015)
The recent evidence from Eastern Europe suggests that one of the major obstacles towards the adoption of euro may lie in the impact that the recession of 2008 exerted on the trajectory of real exchange rates in new member countries (European Commission, 2015). This paper aims to establish and explain the relationship between the external shocks derived from the global financial crisis and recession of 2008 and equilibrium real exchange rate in advanced transition economies of Eastern Europe. The interplay between the external and internal balances is explained by developing an inter-temporal optimizing model of the real exchange rate determination in a small open economy with structural distortions. The results of our model suggest that, in the aftermath of recession, if the Eastern European economies attempt to restore and maintain the balance between the consumption, saving, and investment, the equilibrium real exchange rate will tend to reverse its trajectory from appreciation to depreciation over time in order to encourage a greater production in the future. The equilibrium real exchange rate depreciation in the future may obtain either as a result of an increase in the direct subsidies on investment or as a result of reduced subsidies on the "net-of-investment" income. The deprecation of countries’ real exchange rate, however, may continue to act as an effective constraint against the adoption of euro. © 2015, Institute of Eastern Europe and Central Asia. All rights reserved.
Keywords: Eastern European countries; Real exchange rates; Recession; Subsidies; Transition; dept.eco

Attention on adolescent mental disorders: the long-term effects on labor market outcomes - Yu, Jia (International Journal of Applied Economics, 2019)
According to a presidential task force about national college health in 2005, 14.9% of college students have been diagnosed with depression or anxiety disorders. Almost 75% of them experienced mental health problems during their early childhood or adolescence. Specifically, this paper examines the longitudinal effects of learning disability and attention disorder, and behavior disorder, of children born in 1980 – 1984, on their labor market outcomes as young adults. This study applies data from the National Longitudinal Survey of Youth 1997 (NLSY97), which documents the transition from school to work, and from adolescence to adulthood. By applying a family fixed effects model with Heckman selection procedure and multinomial logistic regression, the research results show that experiencing mental health illness during childhood is associated with a decreased risk of employment, an increased risk of unemployment, and decreased weekly paid working hours. This effect is strong and significant for males, and barely discernible for females. Hence, childhood mental disorder is an important determinant of individual’s labor market outcomes. Targeting the improvement for boys’ mental illness situation might be beneficial for improving their labor market participation.
Keywords: dept.eco; peer-reviewed; ⛔ No DOI found

Are hedge fund returns affected by media coverage of macroeconomic news? - Dutta, Sandip; Thorson, James (Studies in Economics and Finance, 2019)
Purpose: Extant literature suggests that the difficulty associated with the interpretation of macroeconomic news announcements by the market in general in different economic environments, might be the reason why most studies do not find any significant relationship between real-sector macroeconomic variables and financial asset returns. This paper aims to use a different approach to measure macroeconomic news. The objective is to examine if a different measure of a macroeconomic news variable, constructed from media coverage of the same, significantly affects hedge fund returns. Design/methodology/approach: The authors use a news index for unemployment, which is a real-sector variable, constructed from newspaper coverage of unemployment announcements and examine its impact on hedge fund returns. Findings: Contrary to the other studies that examine the impact of macroeconomic news on hedge fund returns, the authors find that media coverage of unemployment news announcements significantly affects hedge fund returns. Practical implications: Overall, this paper demonstrates that the manner in which the market interprets macroeconomic news announcements in different economic environments is probably a more relevant factor for hedge funds and is more likely to impact hedge fund returns. In conjunction with variables – constructed from media coverage of unemployment news announcements – that factor in the manner of interpretation, it is found that surprises also matter for hedge fund returns. This is an important consideration for hedge fund managers as well. Originality/value: To the best of the authors’ knowledge, this is the first study that examines the impact of media coverage of macroeconomic news announcements on hedge fund returns and finds significantly different results with real-sector macro variables. © 2019, Emerald Publishing Limited.
Keywords: Finance; Financial economics; dept.eco; dept.fin; peer-reviewed

Pre-play learning and the preference reversal phenomenon - Kim, Younjun; Hoffman, Elizabeth (Southern Economic Journal, 2018)
Elicited preference rankings for two lotteries are typically inconsistent across choice and pricing tasks. We test whether pre-play learning makes preference rankings consistent. Pre-play learning denotes ex-ante lottery learning, where subjects observe playing lotteries before making decisions. We find that pre-play learning makes the average selling prices for the p-bet, of subjects who choose the p-bet, higher than their average selling prices for the $-bet. However, pre-play learning is not strong enough to equalize the rates of standard and non-standard reversals, although pre-play learning reduces the rate of standard reversals.
Keywords: C91; D12; D81; dept.eco; peer-reviewed

Emission tax and market power - Yoon, Sang Won (Atlantic Economic Journal, 2018)
Keywords: L13; Q00; dept.eco; peer-reviewed

Inflation targeting and monetary policy rules - Patalinghug, Jason C. (Global Economic Observer, 2018)
This paper examines the literature to try to explain the concept of inflation targeting. There are at present two competing monetary policy rules: (1) targeting rules and (2) instrument rules. The objective of this paper is to review the relative merits of these two monetary policy rules. The debate between using either an inflation targeting rule or an instrument rule debate displays the lack of consensus among economists concerning the proper specification and underlying assumptions of the inflation-targeting model which is suited for the analysis of key monetary policy issues. The paper also examines what recent studies have found about the effect of inflation targeting on emerging markets. These studies have shown that inflation targeting has been largely beneficial to emerging markets.
Keywords: Central Bank; Instrument Rules; Macroeconomics; dept.eco; peer-reviewed; ⛔ No DOI found

On the impossibility of sustainable growth in a manufacturing based economy - Yoon, Sang Won; Yoon, Chang-Ho (Economic Research-Ekonomska Istraživanja, 2018)
This paper investigates a possibility of sustainable growth in a multi-output endogenous growth framework where the capital accumulation takes place mainly through the production of the dirty manufactured goods. It is shown that in a closed economy, economic growth is not environmentally sustainable, even under an optimal pollution tax unless the consumption elasticity of substitution between clean and dirty goods approaches infinity as in a small open economy which exports dirty goods. There exists a minimal threshold level of the ratio of clean to dirty capital that ensures sustainable growth in a closed economy.
Keywords: Kuznets curve; Sustainable growth; consumption behavior; dept.eco; economic growth; elasticity; elasticity of marginal utility; elasticity of substitution; environmental Kuznets curve; peer-reviewed; sustainable development

Economic nationalism in the history of international economics - Grubacic, Sanja; Schuster, Julian (International Journal of Pluralism and Economics Education, 2018)
This paper examines the sources of economic nationalism by a closer examination of the theory and policy of international trade, originating in the 19th century. We compare and contrast the views of British classical writers, the main proponents of trade liberalism, with the writings of Friedrich List, the main proponent of economic nationalism. The focus is on the distributional implications of trade, and the treatment of the benefits that a poor country may derive from trading with a rich country in 19th century economic thought. We also review the current literature on economic nationalism, and find that alternative perspectives emerge from differing views on the benefits and drawbacks of globalisation. We argue that List's approach remains relevant to understanding contemporary economic nationalism because it highlights a historical context in which the adverse distributional implications of foreign trade are likely to provoke nationalist sentiment. © 2018 Inderscience Enterprises Ltd.
Keywords: Distribution; Economic liberalism; Economic nationalism; Free trade; Globalisation; History; Inequality; International economics; List; Malthus; Protectionism; Ricardo; dept.eco; peer-reviewed

Stale economic news, media and the stock market - Birz, Gene (Journal of Economic Psychology, 2017)
I employ a classification of headlines from newspapers and wire services to examine whether stale macroeconomic news affects stock prices. Unlike with individual stocks, the cost of obtaining information about major economic releases is relatively low. Thus, stock prices should adjust to economic news announcements prior to their coverage in newspapers. I find statistically and economically significant relationship between stale news stories on unemployment and next week's S&P 500 returns. This effect is then completely reversed during the following week. These findings show that investors are affected by salient information and support the hypothesis that investors overreact to stale macroeconomic news reported in newspapers. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: Attention; Efficient markets; Macroeconomic announcements; Media; Salience; dept.eco; dept.fin

What does improved spectrum management mean for the Philippines? - Patalinghug, Epictetus; Patalinghug, Jason (Annals of the Constantin Brancusi University of Targu Jiu, Economy Series, 2019)
This paper analyzes spectrum management practices in the Philippines. The regulatory body allocates available spectrum via an administrative approach which lacks transparency and due process. The paper recommends that the regulatory body adopts the auction method in allocating spectrums which is more transparent, fair, and cost-effective if a suitable design is adopted.
Keywords: Allocation Methods; Auction; Philippines; Spectrum Management; dept.eco; ⛔ No DOI found

Examining the dynamic linkages of performance and volatility of REIT returns - Dania, Akash; Dutta, Sandip (The Journal of Wealth Management, 2017)
This article extends the literature on the financial performance of real estate investment trusts (REITs) by examining whether U.S. REIT returns are impacted by global REITs and other real estate subsectors, such as the U.S. Real Estate Index (USRE) and the U.S. Mortgage Finance Index (USMF). The authors also explore the issue of volatility transmission and the asymmetric effect of volatility spillover on U.S. REIT returns from innovations originating in other real estate subsectors and Global REITs. Results suggest that U.S. REITs are impacted by USRE and USMF returns. There is also evidence of volatility spillover from key real estate constituents-that is, USRE and USFM returns and global REIT markets. These results can be attributed to the changing dynamics of the real estate sector and the gradual integration of the global real estate sector as an asset class. These findings have strong implications for constructing global portfolios including REITs.
Keywords: dept.eco; dept.fin

Broadband internet and new firm location decisions in rural areas - Kim, Younjun; Orazem, Peter F. (American Journal of Agricultural Economics, 2017)
Keywords: dept.eco; peer-reviewed

Comparison of Single-Payer and Non Single-Payer Health Care Systems: A Study of Health Administration Efficiency - Yu, Jia; Zhang, Yi (Modern Economy, 2017)
The United States spends nearly twice as much per capita on health care as several OECD countries. Based on previous research, universal health care decreases the total health care expenditure due to the single-payer system; it is still unknown whether a mixed health care system has superiority. In this study, we compare and evaluate both quality of care and administrative costs among six developed countries, upon three groups: single-payer universal health care system (Australia and Canada), two-tier health care system (France and Japan), and insurance mandate health care system (Switzerland and the US). The results show that both single-payer system and two-tier system are superior to insurance mandate system on health insurance administration costs. Also, regarding insurance mandate system, the healthcare system in Switzerland is more efficient than that in the US. So, we conclude that it is possible for the US to choose a diverse healthcare system, instead of focusing on one system, to trim the healthcare administration cost and improve the quality of care for the entire country.
Keywords: dept.eco